Engaging high school students about organ donation and transplantation: an evaluation of the High School Outreach Initiative (HSOI) program. (18th February 2021) - Selvanathan, Cynthia; Famure, Olusegun; Batoy, Benedict; Cocco, Anna; So, Stephanie; Breckbill, Kathryn; Meliton, Galo; Norgate, Andrea; Kim, Sang Joseph; Ng, Vicky Lee
Abstract: Adolescents can be influential in changing societal perceptions of organ donation and transplantation (ODT) but current studies on youth are limited. We sought to (1) assess the baseline knowledge in ODT among students in Toronto, Canada, and (2) evaluate the effectiveness of the High School Outreach Initiative (HSOI) program presentations in changing awareness and interest about ODT. Pre‐ and post‐presentation surveys were administered to high school students about their knowledge of ODT, awareness of donor registration, importance of donation, intent to register, and willingness to talk to their families about donation. Descriptive statistics were used to characterize the students' baseline knowledge and interest. Wilcoxon and McNemar tests were used to analyze changes in perceptions before and after the presentation. A total of 449 HSOI presentations were delivered to 33, 090 students at 102 high schools in the Greater Toronto Area between 2012 and 2019. Data from 3327 surveys completed by students before a presentation showed 46.5% were not knowledgeable about ODT. For the 2‐year period between 2017 and 2019, 1224 matched pre‐ and post‐presentation surveys were collected. The 49.8% of students who stated they were not knowledgeable about ODT prior to the presentation decreased to 3.8% after ( p < 0.001). Those who were not willing to register decreased by half after the presentation ( p < 0.001). The HSOI is an effective educational program in improving youth's attitudes and perceptions toward ODT. Further directions of the program include the expansion to other cities and the collection of demographic information of students.